The effect of paylean on nursery pig performance - N Z Frantz; Robert D Goodband; Jim L Nelssen; Joel M DeRouchey; Michael D Tokach; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2005)
A 28-d growth study with a total of 192 weanling pigs (PIC 210 × L42, 21 ± 2 d of age and 14.6 lb initial BW) was conducted to determine the effects on nursery pig performance resulting from feeding Paylean (5 ppm) for 3, 7, or 14 d after weaning. A Phase 1 diet containing 15% spray-dried whey, 3.75% fish meal, and 3% soybean oil was fed to all pigs for the initial 14 d. The diet contained 1.55% lysine, and DL-methionine and L-threonine were added to maintain minimum amino acid ratios. The dietary treatments were formulated with or without Paylean (5 ppm) replacing corn starch. All pigs were fed a Phase 2 diet based on corn and soybean meal, without added specialty ingredients, from d 14 to 28. From d 0 to 3, pigs fed the control diet had increased ADFI (P<0.05), compared with those fed Paylean. From d 0 to 7, as duration of Paylean feeding increased, ADG decreased (linear, P<0.01) and F/G became poorer (linear, P<0.01). Pigs fed Paylean had reduced ADFI (P<0.04), compared with that of pigs fed the control diet. From d 0 to 14, as duration of Paylean feeding increased, ADG (linear, P<0.01) and ADFI (linear, P<0.05) decreased and F/G became poorer (linear, P<0.01). There were no differences in ADG, ADFI, or F/G (P>0.23) when a common Phase 2 diet was fed from d 14 to 28 after weaning. Overall, d 0 to 28, ADG decreased (linear, P<0.05) and F/G became poorer (linear, P<0.05) as duration of Paylean feeding increased. Average daily feed intake was unaffected by duration of Paylean feeding (P>0.13). In addition, as duration of Paylean feeding increased from 0 to 14 d, ending weights tended to decrease (linear, P<0.06). In conclusion, feeding Paylean to nursery pigs after weaning reduced performance, and the reduction was greater the longer it was fed after weaning. Paylean should not be fed to newly weaned nursery pigs.; Swine Day, 2005, Kansas State University, Manhattan, KS, 2005
Keywords: Swine day; 2005; Summary Publication of Report of Progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 964; Kansas Agricultural Experiment Station contribution; no. 06-63-S; Swine; Paylean; Weanling pig